POLITENESS STRATEGIES PERFORMED BY JAMES BONDIN SKYFALL MOVIE - RACHMAD, ANGGI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Rachmad, Anggi. 2014. Politeness Strategies Performed by James Bond in SKYFALL Movie. Study Program of English. Universitas Brawijaya. Supervisor:Nurul Choyimah; Co-supervisor: Yana Shanti ManipuspikaKeywords: Politeness, Face, Face Threatening Act (FTA).Communication is one of the important things for human as a social creature. In doing the communication people need polite language to give respect to the hearer and maintain a good relationship with the hearer. The writer conducted a study about politeness on SKYFALL Movie which presents about politeness phenomena happening in life aspect in this modern era. There are two problems to be solved, they are: (1) what FTA strategies are used by main Character James Bond in SKYFALL movie and (2) what politeness strategies are used by main character James Bond in SKYFALL movie.This study used qualitative approach to gather and analyze the data. It isincluded into document analysis in analyzing and interpreting the utterances produced by the main character of SKYFALL movie through the script of the movie.As for the result of this study, it shows that there are four strategies inperforming FTA applied by the main character of the movie, namely: Bald on-record, positive politeness, negative politeness, and indirect strategy. In the application of politeness strategies, Bond mostly used positive politeness in his utterance to show cooperation and effort to minimize the social distance with others. However, he still considers to perform FTA baldly in giving orders to his colleagues.Based on the results, the writer suggests to the next researchers to use otherobjects reflecting more about politeness strategy in daily life and use theories inanalyzing the implicit meanings of the speaker’s utterances more.